Penta‐band circularly polarised antenna using a lumped capacitor. Issue 8 (1st June 2016) - Hoang, The Viet; Le, Tuan Tu; Li, Qui Yu; Park, Hyun Chang
Abstract : A very simple printed monopole antenna with penta‐band circularly polarised (CP) radiation characteristics for wireless local area network (WLAN), worldwide interoperability for microwave access, and downlink of the X‐band satellite communication applications is proposed for the first time. The antenna comprises a notched rectangular ground plane and a radiating patch consisting of inverted‐U‐shaped, I‐shaped, and inverted‐L‐shaped radiators, and creates four CP modes operating at 2.4/3.5/5.8/7.5 GHz frequency bands. By placing a lumped capacitor of 0.5 pF in the gap between the I‐shaped radiator and the inverted‐L‐shaped radiator, an extra CP mode at 5.2 GHz WLAN band is generated, thus completing the penta‐band CP antenna. The measured −10 dB impedance bandwidth of the demonstrated antenna is 340 MHz (2.37–2.71 GHz) and 4.8 GHz (3.2–8 GHz), and the measured 3 dB axial‐ratio bandwidth is 16.6, 13.5, 2.9, 2.4, and 4% in five distinct bands of 2.1−2.48, 3.1−3.55, 5.1−5.25, 5.76−5.9, and 7.45−7.75 GHz.